Diabetic patients treated with novel thin composite-wire strut zotarolimus-eluting stents versus ultrathin strut sirolimus-eluting stents in the BIONYX trial: 2-year results of a prespecified analysis. (25th November 2020) - Ploumen, E; Buiten, R.A; Zocca, P; Roguin, A; Doggen, C.J.M; Jessurun, G.A.J; Schotborgh, C.E; Danse, P.W; Benit, E; Aminian, A; Van Houwelingen, K.G; Stoel, M.G; et al.
Abstract: Background/Introduction: The novel thin composite-wire strut zotarolimus-eluting stent (ZES) is a drug-eluting stent that is frequently used for treating patients with obstructive coronary artery disease, but so far no clinical outcome data have been published in patients with diabetes. In all-comer patients, the BIONYX trial (NCT02508714) has established non-inferiority of the ZES versus the ultrathin strut biodegradable-polymer sirolimus-eluting stent (SES) regarding the primary composite endpoint of target vessel failure at 1 year follow-up. Purpose: To assess in patients with diabetes, the 2-year safety and efficacy of the current generation thin composite-wire strut ZES, compared to the ultrathin strut SES. Methods: In the international, multicentre BIONYX trial, randomisation was stratified for sex and the presence of diabetes mellitus. We performed a prespecified subgroup analysis of patients with diabetes. The main endpoint target vessel failure was a composite of safety and efficacy, consisting of cardiac death, target vessel-related myocardial infarction or clinically indicated target vessel revascularisation. Secondary endpoints, such as target lesion revascularisation and stent thrombosis were also assessed. Results: A total of 510/2488 (20.5%) BIONYX trial participants had diabetes, and were therefore included in this analysis. Patients were on average 66.4±10.3 years old, and 28.6% were female. Most participants presented with acute coronary syndromes (65.1%), and 182/510 (35.7%) patients were insulin dependent. Two-year follow up was available in 500 of 510 (98.0%) patients. Target vessel failure occurred in 31/260 (12.2%) patients assigned to ZES versus 26/250 (10.7%) patients assigned to SES (HR 1.14, 95%-CI 0.68–1.92; P-logrank=0.63). Kaplan Meier curves of target vessel failure are displayed in Figure 1. There were no significant between-stent differences in the individual components of this endpoint. Target lesion revascularisation occurred in 15/260 (6.0%) patients treated with ZES versus 9/250 (3.7%) patients treated with SES (HR 1.61, 95%-CI 0.71–3.68; P-logrank=0.25). Definite stent thrombosis was an infrequent event and did not differ significantly between stent-arms (0.4% vs. 1.2%; HR 0.32, 95%-CI 0.03–3.06; P-logrank=0.30). Conclusion: In patients with diabetes, the novel thin composite-wire strut durable polymer ZES was similarly safe and efficacious as compared to the ultrathin cobalt-chromium strut biodegradable-polymer SES at 2-year follow-up. Funding Acknowledgement: Type of funding source: Private company. Main funding source(s): The BIONYX trial was equally funded by Biotronik and Medtronic.